Rupturas epistemológicas e o discurso sobre Deus. Uma leitura a partir de Michel Foucault. (Epistemological ruptures and discourse about God. A reading from Michel Foucault.) - DOI: 10.5752/P.2175-5841.2010v8n18p27 - Ribeiro, Flávio Augusto Senra (Horizonte, 2010)
The article presents the results of research that investigate on epistemological ruptures and speaking about God in The Order of Things writhed by Michel Foucault. Entitled as "God, words and things," this research partially presented here is intended as collaboration for the analysis of what has been identified as phenomenon of neo-atheism, a topic very important for the Philosophy of Religion today. To understand it, we present, following the Foucaultian perspective, the different epistemological nuances underpinning conception of God. In her three moments, the text presents the Renaissance episteme and the God's discourse, the classical episteme and the idea of God and, finally, the modern episteme, the death of God and man's death. It is believed that what is decided in the contemporary is not necessarily the finish time of the death of God and the consequent man's death, the fruit of modern way of understanding and themes on the divine, the infinite, the absolute or true, but a clear dispute between different epistemological perspectives in their political, cultural and religious diversity achievements.